EVALUATION OF FLOW DISTRIBUTION IN THE PELLETIZING FURNACE THROUGH CFD AND EXPERIMENTAL VALIDATION AT SAMARCO - Maycon Athayde; Roberto Parreiras Tavares; Sergio Fernando Nunes; Maurício Cota Fonseca (Tecnologia em Metalurgia, Materiais e Mineração, 2014)
Samarco produces iron ore pellets thermally processed in Travelling Grate furnaces. This process is essential in order to obtain adequate mechanical strength to the pellets transportation and operation in the reduction reactors. All the mechanical properties of the agglomerates are obtained during the stage of firing, being a decisive step to pellet quality. Therefore, the velocity distribution of gas flow within this zone must be homogeneous. For this reason, it was developed a mathematical CFD model to characterize the gas flow in the burning zone, applying the equations of conservation of momentum, mass and energy. The validation of the model was obtained by measuring the temperatures inside the furnace. It was developed a wireless communication system in order to monitor continuously the evolution of the temperatures in the furnace.